Im Namen der Dinge - Wörner, David (Medieval and Early Modern Philosophy, 2019)
The main assumption of this book is that Locke's methaphysical considerations spread throughout his works build a coherent metaphysical theory about the essence of things. Contrary to prevalent opinions, Locke thereby proves to be a philosopher who not only criticised the metaphysical systems of the late scholasticism, but also advanced them in a very interesting way.